Wearable Pressure Sensor Array for Health Monitoring - Matti Kaisti; Joni Leppänen; Olli Lahdenoja; Mikko Pänkäälä; Tero Koivisto; Ulf Meriheinä (United States, 2022)
Measuring the arterial waveform in real-time using wearable devices mounted directly on skin holds promise in assessing cardiovascular health status and detecting an early onset of cardiovascular disease. We report the use of modern high performance MEMS pressure sensors for wearable health monitoring. The low-cost sensor elements were incorporated onto a ﬂexible wristband for radial artery pulse measurement. These sensor elements were conﬁgured as an array and attached to a wristband. The device operation was tested on 13 healthy subjects and from each subject we successfully derived the average arterial waveform, located the diastolic and systolic peaks together with Dicrotic notch and calculated the heart rate. In the future, the MEMS pressure sensors might be employed for mobile and remote cardiovascular health monitoring.
Computing in Cardiology